Pilgrim without boundaries - Ravindra Ravi (Chennai Satya Nilayam, 2002)
Ravindra looks at our spiritual quests and reminds us we are each on a journey, with a longing for the Infinite. Some of us wish to speak from a pilgrim soul to another pilgrim soul. In Pilgrim without Boundaries he notes the restlessness in one, but a w
Keywords: Religion-philosophy and theory